Pre-clinical and clinical importance of miR-21 in human cancers: Tumorigenesis, therapy response, delivery approaches and targeting agents. (January 2023) - Hashemi, Mehrdad; Mirdamadi, Motahare Sadat Ayat; Talebi, Yasmin; Khaniabad, Nasrin; Banaei, Gooya; Daneii, Pouria; Gholami, Sadaf; Ghorbani, Amin; Tavakolpournegari, Alireza; Farsani, Zoheir Mohammadian; Zarrabi, Ali; Nabavi, Noushin; et al.
Abstract: The field of non-coding RNA (ncRNA) has made significant progress in understanding the pathogenesis of diseases and has broadened our knowledge towards their targeting, especially in cancer therapy. ncRNAs are a large family of RNAs with microRNAs (miRNAs) being one kind of endogenous RNA which lack encoded proteins. By now, miRNAs have been well-coined in pathogenesis and development of cancer. The current review focuses on the role of miR-21 in cancers and its association with tumor progression. miR-21 has both oncogenic and onco-suppressor functions and most of the experiments are in agreement with the tumor-promoting function of this miRNA. miR-21 primarily decreases PTEN expression to induce PI3K/Akt signaling in cancer progression. Overexpression of miR-21 inhibits apoptosis and is vital for inducing pro-survival autophagy. miR-21 is vital for metabolic reprogramming and can induce glycolysis to enhance tumor progression. miR-21 stimulates EMT mechanisms and increases expression of MMP-2 and MMP-9 thereby elevating tumor metastasis. miR-21 is a target of anti-cancer agents such as curcumin and curcumol and its down-regulation impairs tumor progression. Upregulation of miR-21 results in cancer resistance to chemotherapy and radiotherapy. Increasing evidence has revealed the role of miR-21 as a biomarker as it is present in both the serum and exosomes making them beneficial biomarkers for non-invasive diagnosis of cancer. Graphical Abstract: ga1